Goal-oriented gaze strategies afforded by object interaction. (January 2015) - Belardinelli, Anna; Herbort, Oliver; Butz, Martin V.
Highlights: We conducted an eyetracking experiment comparing a perceptual and two action tasks. Scanpaths and attention maps show significant differences on task-relevant points. ROI-based metrics show how the eyes land in between the finger grasping points. Salient features correlate with affordances and could be exploited by the visual system. Abstract: Task influence has long been known to play a major role in the way our eyes scan a scene. Yet most studies focus either on visual search or on sequences of active tasks in complex real world scenarios. Few studies have contrasted the distribution of eye fixations during viewing and grasping objects. Here we address how attention is deployed when different actions are planned on objects, in contrast to when the same objects are categorized. In this respect, we are particularly interested in the role every fixation plays in the unfolding dynamics of action control. We conducted an eye-tracking experiment in which participants were shown images of real-world objects. Subjects were either to assign the displayed objects to one of two classes (categorization task), to mimic lifting (lifting task), or to mimic opening the object (opening task). Results suggest that even on simplified, two dimensional displays the eyes reveal the participant's intentions in an anticipatory fashion. For the active tasks, already the second saccade after stimulus onset was directed towards the central region between the two locations where the thumb and the rest of the fingers would be placed. An analysis of saliency at fixation locations showed that fixations in active tasks have higher correspondence with salient features than fixations in the passive task. We suggest that attention flexibly coordinates visual selection for information retrieval and motor planning, working as a gateway between three components, linking the task (action), the object (target), and the effector (hand) in an effective way.